Eravacycline (TP-434) Is Efficacious in Animal Models of Infection - Grossman, Trudy H. (Antimicrob Agents Chemother, 2015)
Eravacycline is a novel broad-spectrum fluorocycline antibiotic being developed for a wide range of serious infections. Eravacycline was efficacious in mouse septicemia models, demonstrating 50% protective dose (PD(50)) values of ≤1 mg/kg of body weight once a day (q.d.) against Staphylococcus aureus, including tetracycline-resistant isolates of methicillin-resistant S. aureus (MRSA), and Streptococcus pyogenes. The PD(50) values against Escherichia coli isolates were 1.2 to 4.4 mg/kg q.d. In neutropenic mouse thigh infection models with methicillin-sensitive S. aureus (MSSA) and S. pyogenes, eravacycline produced 2 log(10) reductions in CFU at single intravenous (i.v.) doses ranging from 0.2 to 9.5 mg/kg. In a neutropenic mouse lung infection model, eravacycline administered i.v. at 10 mg/kg twice a day (b.i.d.) reduced the level of tetracycline-resistant MRSA in the lung equivalent to that of linezolid given orally (p.o.) at 30 mg/kg b.i.d. At i.v. doses of 3 to 12 mg/kg b.i.d., eravacycline was more efficacious against tetracycline-resistant Streptococcus pneumoniae in a neutropenic lung infection model than linezolid p.o. at 30 mg/kg b.i.d. Eravacycline showed good efficacy at 2 to 10 mg/kg i.v. b.i.d., producing up to a 4.6 log(10) CFU reduction in kidney bacterial burden in a model challenged with a uropathogenic E. coli isolate. Eravacycline was active in multiple murine models of infection against clinically important Gram-positive and Gram-negative pathogens.